Enhancing Student Satisfaction in Educational Management: a Bayesian Analysis of Influential Factors and Improvement Strategies - Sheng, Wang; Fan, Zhongyi; Weng, Shiyang (Journal of the knowledge economy, 2025)
Since the 1980s, higher education has progressively occupied an expanding portion of social resources, while its contributions to society continue to grow. The quality of higher education and college students’ satisfaction with educational management, along with the factors influencing them, has long been pivotal concerns in the realm of education. Within the academic community, there has been a growing recognition of the importance of assessing higher education management through the lens of student satisfaction. However, in today’s educational landscape, students hold diverse opinions regarding teaching quality within colleges. To address this situation, this paper employs Bayesian statistical methods to investigate and analyze the determinants of college students’ satisfaction with educational management. The study further utilizes factor analysis, regression analysis, and evaluation scoring methods to discern the influencing factors behind educational management satisfaction. The findings reveal that 36.60% of students possess a general understanding of the subject, while 14% have no understanding at all, thereby impacting their comprehension of teaching management. Additionally, insufficient attention to teaching management information affects students’ cognizance of this domain, with 62% of students occasionally paying attention and 35% never doing so. These current circumstances inevitably affect students’ evaluations of teaching management satisfaction. Consequently, higher education institutions must establish more direct lines of communication with students and employ methods that students are willing to engage with, utilizing multi-channel and multi-level approaches to elevate students’ cognitive grasp of teaching management.